Literatur Review Faktor-faktor Yang berhubungan dengan Keluhan Musculoskeletal Disorders (MSDS) pada Pekerja Bagian Packing Tahun 2025 - Mangiring, Paul (CV. Green Publisher Indonesia, 2025)
Musculoskeletal Disorders are disorders experienced by a person from mild complaints to pain Severe in the joints, nerves, muscles and bones. Behind the consequences of unnatural work. Preliminary study results on CV. Sada Wahyu found that workers experienced complaints in 9 sections Main body. This occurs due to the position of the back which bends at an angle of 88˚ during work. Repeated work processes for a long time. The average age of workers is ≥35 Years and average service life ≥5 years. The purpose of this study was to determine the relationship between posture Work, age and years of service with Musculoskeletal Disorders (MSDs) complaints in workers. This type of research is quantitative research with a design Cross sectional research. The sample is 42 people. The sampling technique uses totality Sampling. The instrument analyzes work posture on the incidence of Musculoskeletal Disorders complaints Is the Rapid Entrie Body Assessment sheet. To see complaints of Musculoskeletal Disorders using the Nordic Body Map sheet. Chi square test data analysis. Bivariate analysis shows There is a relationship between work posture and complaints of Musculoskeletal Disorders in p-value workers (0.033<0.05). There is a relationship between age and complaints of Musculoskeletal Disorders in workers p-value (0.012 <0.05), and there is a relationship between length of work and Musculoskeletal complaints Disorders on workers p-value (0.009 < 0.05). There is a statistical relationship between work posture, Age and years of service with Musculoskeletal Disorders complaints in workers.